Microbial exopolymers for soil restoration and remediation: current progress and future perspectives - Punsaldulam, Dashnyam; Amumandal, Orgil (Proceedings of the Institute of Biology, 2023)
Soil degradation and pollution are pervasive global challenges caused by climate change and anthropogenic activities. To address these issues, seeking environmentally friendly and sustainable solutions to restore degraded soils and remediate polluted ones is imperative. One promising avenue lies in the utilization of microbial exopolymers, which can play a pivotal role in rejuvenating soil health by enhancing its physical, chemical, and biological properties. Microbial exopolymers, through their various functional groups, facilitate interactions that bind soil particles together, thereby promoting soil aggregation and immobilizing soil pollutants. Thus, the application of exopolymers holds the potential to enable soils to continue providing its essential ecosystem services. Despite significant progress in evaluating the impact of microbial exopolymers on soil properties, there remains a pressing need to overcome existing challenges that hinder the large-scale use of microbial exopolymers for soil restoration and remediation. The significant challenges include (i) inadequate understanding on the effectiveness and safety of exogenous microorganisms and their interactions with native soil biotic and abiotic factors, (ii) the lack of feasible methods for characterizing the constituents of exopolymers produced by soil microbial community, (iii) insufficient efforts in exploring the community diversity of soil microorganisms capable of producing exopolymers in various soils, and (iv) inadequate effort on aligning the molecular characteristics of exopolymers with the specific application purposes. To harness the full potential of microbial exopolymers, interdisciplinary approaches are paramount in achieving improved effectiveness of soil restoration and bioremediation endeavors, which are of utmost importance in the ever-changing environment. Бичил биетний экзополимерийг хөрсний нөхөн сэргээлтэд ашиглах нь: өнөөгийн төлөв байдал, ирээдүйн чиг хандлага Хураангуй. Уур амьсгалын өөрчлөлт болон хүний үйл ажиллагааны нөлөөгөөр явагдаж буй хөрсний доройтол, бохирдол нь дэлхий нийтийн тулгамдсан асуудлууд бөгөөд эдгээрийг хүрээлэн буй орчинд ээлтэй, тогтвортой технологийн тусламжтай шийдвэрлэх шаардлагатай. Бичил биетний экзополимерийг ашиглан хөрсний физик, хими, биологийн шинж чанарыг нь сайжруулах замаар хөрсний эрүүл төлөв байдлыг нэмэгдүүлэх технологийг боловсруулах боломжтой. Бичил биетний экзополимер нь төрөл бүрийн функциональ бүлгийнхээ тусламжтай хөрсний жижиг хэсгүүдийг холбож барьцалдуулан хөрсний агрегацийг нэмэгдүүлж, хөрс бохирдуулагч нэгдлүүдийг идэвхгүй (тогтвортой) болгодог. Ингэснээр хөрсөөр хангагддаг экосистемийн үүргүүд хэвийн үргэлжлэх боломж бүрдэх юм. Бичил биетний экзополимер хөрсний шинж чанарыг сайжруулдаг болохыг баталсан олон судалгаа хийгдсэн боловч тэдгээрийг хөрсний нөхөн сэргээлтэд өргөн хүрээгээр ашиглахын тулд анхаарах шаардлагатай хэд хэдэн асуудлууд байна. Үүнд: 1. Гаднаас нэмж буй бичил биетэн байгалийн хөрсөнд үр дүнтэй ажиллах эсэх болон тухайн хөрсний хэвийн микробиотад яаж нөлөөлөх талаарх ойлголт хангалтгүй, 2. Хөрсний бичил биетний бүлгэмдлийн ялгаруулж буй эзкополимерийн бүрэлдэхүүн хэсгүүдийг таньж тодорхойлоход хүндрэлтэй, 3. Шинж чанар, эрүүл төлөв байдлын хувьд ялгаатай хөрсөнд эзкополимер нийлэгжүүлэгч бичил биетний олон янз байдлыг харьцуулсан судалгаа маш бага, 4. Экзополимерийн химийн бүтэц, шинж чанарыг хэрэглэж буй зорилготойгоо уялдуулахад бага анхаарч байна. Бичил биетний экзополимерийг бүрэн ашиглаж хөрсний нөхөн сэргээлтийн үр дүнг нэмэгдүүлэхэд салбар дундын судалгаа чухал байна. Түлхүүр үгс: хөрсний агрегаци, хөрсний бичил биетний экзополимер, хөрсний биоремедиаци, хөрсний эрүүл төлөв байдал